2011
DOI: 10.1371/journal.pntd.0001362
|View full text |Cite
|
Sign up to set email alerts
|

The Cost of Antibiotic Mass Drug Administration for Trachoma Control in a Remote Area of South Sudan

Abstract: BackgroundMass drug administration (MDA) of antibiotics is a key component of the so-called “SAFE” strategy for trachoma control, while MDA of anthelminthics provides the cornerstone for control of a number of other neglected tropical diseases (NTDs). Simultaneous delivery of two or more of these drugs, renowned as “integrated NTD control,” is being promoted to reduce costs and expand intervention coverage. A cost analysis was conducted alongside an MDA campaign in a remote trachoma endemic area, to inform bud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 27 publications
1
22
0
Order By: Relevance
“…Enhancing coverage via an extra treatment visit to each community cost a further $0.04 per head, improved coverage in 0–9 year-olds by about 3%, but had no effect on outcome and, in this setting, was not worthwhile. The treatment costs are less than the $ 1.53 per head reported in South Sudan [ 18 ], but similar to the $ 0.25 estimate from Mali [ 19 ]. A cost of ≤$0.50 per person for trachoma treatment has been quoted in the literature when assessing programme sustainability or cost savings through integrated treatment campaigns targeting several neglected tropical diseases [ 18 , 20 , 21 ].…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Enhancing coverage via an extra treatment visit to each community cost a further $0.04 per head, improved coverage in 0–9 year-olds by about 3%, but had no effect on outcome and, in this setting, was not worthwhile. The treatment costs are less than the $ 1.53 per head reported in South Sudan [ 18 ], but similar to the $ 0.25 estimate from Mali [ 19 ]. A cost of ≤$0.50 per person for trachoma treatment has been quoted in the literature when assessing programme sustainability or cost savings through integrated treatment campaigns targeting several neglected tropical diseases [ 18 , 20 , 21 ].…”
Section: Discussionsupporting
confidence: 69%
“…The main drivers were personnel costs followed by supervision. Others have also found personnel to be the major cost from all cost categories in population-based prevalence surveys [ 22 ] and trachoma mass antibiotic treatment distributions [ 18 ]. Interestingly, both these studies found transportation to be the next most expensive cost category after personnel, whereas it was not a major cost in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Few, however, look at time spent by CDDs in distributing health packages [ 31 ]. Furthermore, the costs of CDD involvement in programmes is rarely valued nor included in programme economic evaluations [ 32 , 33 ]. In this study, time allocated by the CDDs towards their NTD Programme duties were a significant factor affecting their performance.…”
Section: Discussionmentioning
confidence: 99%
“…Integrating trachoma programs with other neglected tropical diseases may prove cost-effective, since close to 95% of drug distribution costs have been attributed to recurring costs (personnel, travel, etc. )[78]. However, overlap between diseases would need to be considered to ensure effective integration.…”
Section: Resultsmentioning
confidence: 99%